THE EFFECTIVENESS OF THE USE OF SCIENCE TECHNOLOGY AND COMMUNITY METHODS IN DEVELOPING SOFT SKILLS OF STUDENTS AT SMP NEGERI 4 BANGSALSARI - Fatdriatun Ismah; Depict Pristine Adi (SOLIDARITY: Journal of Social Studies, 2022)
This study aims to obtain a soft skill profile after the implementation of the science technology and society learning method. This is an illustration of the effectiveness of a learning method, one of which is the method of science, technology and society. The use of this research method uses a qualitative method where this research produces information through observation by looking at the performance of the use of this research method using the subject of SMP Negeri 4 Bangsalsari students. So it can be seen that the method of science, technology and society has effectiveness in developing the soft skills of students at SMP Negeri 4 Bangsalsari Jember. In other words, varied learning such as learning models of science, technology and society can improve ways of thinking, working together and solving problems.